(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background: Choledochal Cyst are congenital dilatation of the biliary system including the common, intrahepatic and intrapancreatic bile duct. Cysts have a tendency for complication and high risk of malignant changes over time. Surgery is the treatment of choice. We present our surgical experience of choledochal cyst excision with bilioenteric anastomosis. Methods: A total 78 Choledochal cyst cases that underwent surgery at our hospital were included in the study. Cysts were classified according to the Todani modification of the Alonso Lej classification. Surgical management included Choledochal cyst excision followed by bilioenteric anastomosis in form of Roux-en-Y hepaticojejunostomy. Anastomotic patency and liver function tests were checked in all patients before transanastomotic tube removal. Results: Mean age of study subject was 16.67 years with most cases below 20 years age. Female preponderance was seen among study cases with 56 (71.79%) female and 22 male patients. Most common presenting complaint was abdominal pain 60 (76.92%), followed by jaundice 32 (41.03%), nausea/vomiting in 20 (25.64%), palpable mass 18 (23.06%) and cholangitis with fever in 16 (20.51%) patients. Pancreatitis was observed in 15 (19.23%) patients. Prior history of cholecystectomy was seen in 12 (15.38%) of cases. In 78 cases (Type I, and IVb) included in our study, cyst excision was done followed by Roux-en-Y hepaticojejunostomy. Surgical site infections were reported in 5 cases (6.4%), transient bile leak which was treated conservatively in 1 case (1.25%) and intra-abdominal collections seen in 2 cases (2.5%). No mortality was reported in present study. Malignancy (Cholangiocarcinoma) was seen in 1 case (0.9%). A satisfactory Anastomotic patency and liver function tests were achieved in all patients after 3 weeks of surgery, when transanastomotic tube was removed. Conclusion: Choledochal cyst require an accurate diagnosis and surgical treatment in order to decrease the risk of complications which includes malignant transformation and progression of the disease. Most cases of choledochal cysts are Type I and IV cyst that can be treated with good results by early surgical excision of the cyst followed by bilioenteric continuity preferably by Roux-en-Y hepaticojejunostomy.